IMPLEMENTASI AKAD MURABAHAH DAN PERMASALAHANNYA DALAM PERBANKAN SYARIAH - Raihan Putri; Fitri Yanti (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
Murabahah is a sale and purchase contract with additional profits in accordance with the agreement. This study aims to further analyze the application of murabaha contracts in Islamic banking, as well as answer how the murabaha concept actually is and then look at the implementation of murabaha financing in banks whether it is appropriate based on sharia principles or not. This study used a qualitative descriptive research method through a library study data collection technique. As for the discrepancies found in the application of murabahah financing in Islamic banking, namely regarding violations related to milkiyah requirements. The results of the study show that the implementation of murabahah contract financing does not meet the pillars and conditions of sale and purchase in accordance with sharia principles. If the bank wishes to represent the customer, the solution is that the item must change ownership, the object of the transaction must be fully controlled by the bank before making a transaction.